THE ROLE OF CITIZENSHIP EDUCATION IN PREVENTING ETHNIC CHINESE BULLYING POST COVID-19 PANDEMIC IN ISLAMIC SCHOOLS - Ervina Halit; Muhammad Turhan Yani; Harmanto (International Journal of Social Science, 2024)
The aim of this research is to find out and analyze further regarding 1) How bullying behavior towards ethnic Chinese occurs after the Covid-19 pandemic in Islamic schools, 2) What is the role of Framing Media regarding the Covid 19 pandemic which encourages bullying behavior towards ethnic Chinese in Islamic schools , 3) How does citizenship education prevent bullying of ethnic Chinese after the Covid-19 pandemic in Islamic schools. This research uses qualitative methods to obtain theories and argumentative bases based on the results of literature research from various sources such as magazines, articles and books and related to the problems to be solved. As we know, currently many teenage attitudes are emerging that are contrary to multiculturalism. Among them, bullying behavior often occurs, especially among school children. Bullying is said to be a form of child abuse carried out by peers of the same age against someone (child) who is "lower" or weaker in order to gain their own advantage or satisfaction. Bullying behavior that often occurs in school children is verbal, for example mocking the ethnicity of other students. Therefore, Citizenship Education in schools is expected to improve good character in students and can encourage students to understand and be able to carry out their rights and obligations in becoming good, intelligent, skilled and responsible citizens, especially through the values ​​of Pancasila which contain many human values. Based on the research results, it was found that: 1) Bullying behavior towards ethnic Chinese after the Covid-19 pandemic in schools occurred because the character of mutual respect for multiculturalism had not yet developed and lack of wisdom in consuming communication media, especially online media. 2) Media has an important role in building anti-stigma. China during the Covid-19 pandemic with the Wuhan virus narrative, 3) Citizenship Education is an important subject in preventing bullying behavior in schools with competency achievements in Phase E which teaches building harmony in diversity